ANALYSIS OF THE EFFECT OF FATHERLESSNESS ON DELINQUENT BEHAVIOR AMONG HIGH SCHOOL STUDENTS IN TELUK KUANTAN - Mey Lani Rudita Lia; Silvi Juwita (Causalita, 2025)
This study aims to determine the effect of fatherless on juvenile delinquency in high school students in Teluk Kuantan. The population in this study were students of SMAN, MAN, and SMKN in Teluk Kuantan with a total of 108 students in 4 schools in Teluk Kuantan and the sample used was 108 subjects. The research method used is quantitative with correlational design with quota sampling technique. Data were collected through questionnaires that measured the level of fatherlessness and juvenile delinquency, which were then analyzed using multiple linear regression techniques. The results of the analysis using multiple linear regression techniques obtained the coefficient of determination (R2) = 0.341 with a significance value of p=0.00 (p<0.05), meaning that there is a significant influence between fatherless conditions and juvenile delinquency. So it can be concluded that the higher the level of fatherlessness experienced by a teenager, the greater their tendency to commit deviant behavior. The conclusion of this study confirms that fatherlessness is one of the main factors that influence juvenile delinquent behavior.